The Effect of High-Intensity Interval Training on Interleukin-6 Levels in Hypertensive Individuals: A Systematic Review and Meta-Analysis - Ainnaya Natin Ristanti; Roman Ardian Goenarjo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: High-intensity interval training (HIIT) has emerged as a time-efficient exercise modality with potential benefits for hypertensive individuals. Interleukin-6 (IL-6), a cytokine with both pro- and anti-inflammatory properties, has been implicated in the development and progression of hypertension. This meta-analysis aimed to investigate the effect of HIIT on IL-6 levels in hypertensive individuals. Methods: A systematic search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify relevant studies published between 2013 and 2024. Studies were included if they met the following criteria: (1) randomized controlled trials; (2) included hypertensive participants; (3) compared HIIT to a control group (no exercise or moderate-intensity continuous training); (4) measured circulating IL-6 levels; and (5) provided sufficient data for meta-analysis. Data were extracted and pooled using a random-effects model. Results: Seven studies met the inclusion criteria, comprising a total of 328 participants. The meta-analysis revealed a significant decrease in IL-6 levels following HIIT compared to the control group (standardized mean difference [SMD] = -1.27, 95% confidence interval [CI] = (-1.81 to -0.73, p = 0.002). Subgroup analysis showed that HIIT interventions lasting ≥ 8 weeks were associated with a greater reduction in IL-6 levels compared to shorter interventions. Conclusion: HIIT appears to be an effective exercise modality for reducing IL-6 levels in hypertensive individuals. This finding suggests that HIIT may have anti-inflammatory effects and could be a valuable non-pharmacological strategy for managing hypertension.